HUBUNGAN PERILAKU IBU DENGAN STIMULASI PERKEMBANGAN MOTORIK ANAK USIA PRASEKOLAH DI PAUD MUTIARA HATI SIDODADI DUSUN IV RAHAYU DESA SIDODADI KECAMATAN BIRU-BIRU TAHUN 2022 - manik, maria hermita; -, siti marlina (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2024)
The attitudes that mothers adopt when caring, directing, and advising their children have an impact on them. Children are people who fall inside a specific developmental range, which includes newborns and teenagers. Three to six years old is the preschool age group. The preschool years, often known as the golden or critical periods, are extremely sensitive to their surroundings, are fleeting, and cannot be recreated. There will be a phase in the child's psychosocial development between initiative and guilt. Preschoolers initially study the fundamentals of psychosocial development in order to get ready for a greater social life that is required for adaptation or adjustment. The purpose of this study was to ascertain how preschoolers at PAUD Mutiara Hati Sidodadi Dusun IV Rahayu, Sidodadi Village, District, were stimulated in their motor development in relation to their mothers' conduct. 2022 will see Biru-Biru. This kind of study employs a cross-sectional research design and quantitative analysis. 35 PAUD Mutiara Hati students and a sample of 35 individuals made up the research population. The Total Sampling approach was used for sampling in this study. A chi-square test was employed to analyze the data. The study's findings indicate that 35 respondents (100%), or 14 individuals (40.0%) in the good group, 13 individuals (37.1%) in the pretty good category, and 8 individuals in the not good category, made up the frequency distribution of the duration of maternal conduct. (22.9%). The purpose of this study was to investigate the connection between preschoolers' motor development stimulation and mother conduct. The chi-square test findings revealed a p-value of 0.00 for the association between the length of a mother's behavior and the stimulation of her child's motor development. Thus, it can be inferred from the study's findings that preschool-aged children at PAUD Mutiara Hati Sidodadi Dusun IV Rahayu, Sidodadi Village, District, benefit from stimulation of their motor development when it comes to the length of their mothers' conduct. 2022 will see Blue-Blue.